The Effect of Adding Carrots on the Processing of Mud Cakes - Sri Yulianto Fajar Pradapa; Ayu Dewi Hastuti Pangestu Luhur (Budapest International Research and Critics University, 2022)
This Final Project is entitled “The Effect of The Additional of Carrots toThe Process of a Mud Cake”. The research was intended to identify the quality of the mud cake using carrots as one of the ingredients. The method used in this research is experimental, whereas the type of research used is quantitative. Data collection techniques are subjective assessment including sensory test and preference test. The research suggests that carrots affect the mud cake in taste and color, but they don't affect the texture and scent indicators. The flavors being produced are salty sweet, while the colors are orangish yellow. The texture and scent produced as same as the original mud cake, that is soft and no pores with good scent of cakes. From this research, the respondents like the carrot mud cake.